Oral manifestation and root canal therapy of the patient with mucopolysaccharidosis - Ji-Hye Yoon; Hyo-Il Lee; Ji-Hyun Jang; Sung-Hyeon Choi; Hoon-Sang Chang; Yun-Chan Hwang; In-Nam Hwang; Bin-Na Lee; Won-Mann Oh (Restorative Dentistry & Endodontics)
Mucopolysaccharidosis (MPS) is an inherited metabolic disorder caused by a deficiency in enzymes that participate in the degradation of glycosaminoglycans (GAGs) such as heparin sulfate and dermatan sulfate. Left untreated, patients show progressive mental and physical deterioration due to deposition of GAGs in organs. Death often occurs due to cardiac or respiratory failure before patients reach their early twenties. MPS has several oral and dental manifestations. An enlarged head, short neck, and open mouth associated with a large tongue are major characteristics of MPS patients. Dental complications can be severe, including unerupted dentition, dentigerous cyst-like follicles, malocclusions, condylar defects, and gingival hyperplasia. A 21-year-old female patient with MPS was described in this article, with special emphasis on oral manifestations and dental treatment.